ANALISIS SWOT DALAM PENGEMBANGAN BISNIS: (Studi Kasus pada UMKM Budidaya Jangkrik di Desa Ariyojeding) - Erlangga, Brillian Rama; Suseno, Pangki (Applied Research in Management and Business, 2024)
The purpose of this research is to formulate alternative excellent competitive marketing strategies and appropriate company policies using the SWOT (Strength, Weakness, Opportunity, Threat) analysis method in Ariyojeding Village. SWOT analysis is carried out using the IFAZ matrix which describes the company's strength and weakness factors and the EFEZ matrix which describes the company's opportunity and threat factors. From the results of the data analysis, the total score for the strength, weakness, opportunity and threat factors was obtained, respectively, the highest strength weight was 0.54, the highest weakness weight was 0.27, the highest opportunity weight was 0.56, and the highest threat weight was 0.21. These results place the cricket cultivation business in Ariyojeding Village in quadrant I and the marketing strategy that must be implemented is an aggressive growth strategy.